Phát triển đội ngũ cán bộ quản lí trường mầm non theo tiếp cận phát triển năng lực: Nghiên cứu tại thành phố Thanh Hoá - Mai, Thị Khuyên; Lê, Thị Kim Dung (Tạp chí Giáo dục, 2024)
The team of preschool management staff is an essential factor in determining the success of implementing the policy of fundamental and comprehensive innovation in preschool education. Therefore, to meet the requirements of current preschool education innovation, the management staff must not only meet high requirements on professional qualities and competencies, management and leadership competencies but also satisfy factors on knowledge, skills, attitudes, etc. However, in reality, the development of the management staff has not received adequate attention due attention and still has many shortcomings. The article presents the current situation of developing the team of preschool management staff in Thanh Hoa city according to the competence development approach, thereby proposing five groups of measures. The research results show that the measures groups are considered reasonable and feasible. The research contributes to providing a meaningful source of data, creating a foundation to improve the actual effectiveness of the work of developing the team of management staff at preschool education institutions.